2012
DOI: 10.1038/jes.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary metabolites of 1-nitropyrene as biomarkers for exposure to diesel exhaust in taxi drivers of Shenyang, China

Abstract: Diesel exhaust (DE) is a significant contributor to the toxicity associated with particulate matter (PM). 1-Nitropyrene (1-NP) has been used as a molecular marker for DE, and the urinary metabolites of 1-NP have been proposed as biomarkers for exposure to DE. In this study, several urinary 1-NP metabolites were evaluated for their utility as markers of short-term exposures to DE. The study population was a cohort of 24 taxi drivers from Shenyang, China, who submitted urine samples collected before, after, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…No dose-response was established, however, and determining a clear window of internalized exposure and appearance of the metabolites could be challenging given the large between person variability in marker levels and kinetics observed [17, 33]. The same limitations were observed in a study of other nitropyrene metabolites in taxi drivers occupationally exposed to diesel exhaust [41]. An earlier study reported no significant difference of 1-AP levels in blood, between small samples of workers occupationally exposed to diesel exhaust, and urban and rural populations [15].…”
Section: Discussionmentioning
confidence: 99%
“…No dose-response was established, however, and determining a clear window of internalized exposure and appearance of the metabolites could be challenging given the large between person variability in marker levels and kinetics observed [17, 33]. The same limitations were observed in a study of other nitropyrene metabolites in taxi drivers occupationally exposed to diesel exhaust [41]. An earlier study reported no significant difference of 1-AP levels in blood, between small samples of workers occupationally exposed to diesel exhaust, and urban and rural populations [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the value of direct measurement of 1-NP exposure in air as a surrogate measure of DE exposure, air measurements of 1-NP could be useful to validate biomarkers of exposure to DE including measurements of 1-NP metabolites in urine (a measure of dose aggregated across multiple exposure pathways) (Seidel et al, 2002;Toriba et al, 2007;Miller-Schulze et al, 2013;Morgott, 2014) or measurements of hemoglobin adducts to 1-aminopyrene (a measure of bioactivation that may lead to genotoxic effects) (van-Bekkum et al, 1997;Zwirner-Baier and Neumann, 1999). Moreover, as many of the nitro-arenes, including 1-NP, are mutagenic and carcinogenic (IARC, 2014), measurements of 1-NP and its metabolites may better reflect the carcinogenic properties of DE (Scheepers et al, 1995) and personal susceptibility factors such as polymorphisms in enzymes affecting nitroarene metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This report was the first to demonstrate the presence of OHNAAPs and OHNPs in human urine. The measurement of urinary 1‐NP metabolites was applied in taxi drivers' urine samples collected in China, and their concentrations were greater than metabolite levels previously reported in non‐occupationally exposed subjects (Miller‐Schulze et al, ). The sum of urinary 1‐NP metabolites was associated with personal exposure to 1‐NP and the results suggested that the metabolites reflect recent exposure (Galaviz et al, ).…”
Section: Metabolites Of Polycyclic Aromatic Hydrocarbons and Their Dementioning
confidence: 94%